Analysis of aeromagnetic data for interpretation of seismicity at fayoum-cairo area, egypt (2014)
An aeromagnetic reconnaissance study is presented to delineate the subsurface structure and tectonic setting at the Fayoum-Cairo district, which experienced a damaging earthquake on October 12, 1992 of magnitude (M = 5.7). Analysis of aeromagnetic and seismicity data demonstrate three significant tectonic faults with trending to the NE-SW, NW-SE and E-W. The basement is uplifted in the northern and central parts with a depth of 1.3 km, and deepening in the southern part with a depth of 2.5 km. This is a seismically active zone and historically has experienced damaging earthquakes. In 1847, a damaging earthquake with maximum epicentral intensity (Modified Mercalli Intensity (MMI) = VII) was located there. On the eastern side, earthquake sources are well recognized at different locations. These sources created events of moderate size magnitude M and lt; 5. The focal mechanisms of the major events from these sources are generally strike-slip with normal component. The focal mechanism of the earthquake on October 12, 1992 is normal fault type with strike trends in the NW-SE direction. These fault plane solutions are consistent with the tectonic trends derived from the aeromagnetic data mentioned above and suggest that the new tectonics of northeast Africa is predominant.   Resumen Este estudio presenta una exploración aeromagnética para delimitar la estructura subsuperficial y el marco tectónico del distrito de Fayoum-Cairo, que sufrió un terremoto el 12 de octubre de 1992 de magnitud M=5.7. Los análisis de datos sismicidad y aeromagnéticos señalan tres fallas tectónicas significativas con tendencias NE-SO, NO-SE y E-O. El subsuelo se elevó en el norte y en el centro a una profundidad de 1,3 kilómetros, y se hundió en el sur con una profundidad de 2,5 kilómetros. Esta es una zona sísmicamente activa que en su historia ha tenido terremotos dañinos. En 1847 tuvo lugar un terremoto con intensidad epicentral máxima (escala sismológica de Mercalli) de VII. En el lado este se estudiaron las fuentes de terremotos en diferentes partes. Estas fuentes crearon eventos de magnitud moderada M and lt;5. Los mecanismos focales de los eventos principales en estas fuentes son generalmente fallas de desgarre con componente normal. El mecanismo focal del terremoto del 12 de octubre de 1992 es una falla tipo normal con fuertes movimientos NO-SE. Las soluciones de estas fallas son consistentes con las tendencias tectónicas de los datos aeromagnéticos antes mencionados y sugieren que la nueva tectónica del noreste de África es predominante.